EVALUASI PELAKSANAAN PROGRAM JPKM DI INDONESIA (STUDI EVALUASI) -EVALUATION ON IMPLEMENTATION OF MANAGED CARE APPROACH (JPKM) IN INDONESIA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT Background: The concept of managed care approach have been developed since the first of 80s and have been stated in health act No.23 â 1992 (UU No.23 â 1992), followed by 9 regulation by minister of health (Permenkes and SK Menkes). It was developed 18 manual and guidelines on technical approach. However, during 15 years of implementing the program the data showed that the progress was very slow. Methods: The aim of the study was to determine whether the Managed Care Approach (JPKM) was implemented as described and how well it were working at districts and municipalities. The study was conducted by using multistage random sampling in 4 provinces namely Sumatra Utara, DKI Jakarta, Jawa Tengah, and Sulawesi Selatan. All of the districts (80 districts) at 4 provinces were included in the study. Results: The study was conducted in two stages. The first stage was implementation of JPKM of the 80 districts and municipalities. The second stages involved in-depth case studies in 10 selected districts of the provinces. The study showed that